EDUKASI DIGITAL MARKETING SEBAGAI UPAYA PEMBERDAYAAN DAN PENINGKATAN DAYA SAING UMKM BINAAN DOMPET DHUAFA WASPADA MEDAN - Sundari; Rizal Agus; Chaira Salsabilla; Siti Anggi Annisa; Assyifa Karima; Ocha Amelia; Tamara Rossa Linda; Fatimah Azzahra; Tisa Marliah Amin Pulungan (Jurnal Edukasi Pengabdian Masyarakat, 2026)
Limited digital literacy and low understanding of digital marketing remain major obstacles for MSMEs in improving their business competitiveness. These issues were also found in MSMEs under the guidance of Dompet Dhuafa Waspada Medan, which have been relying on conventional marketing methods. This Community Service (PKM) activity aims to provide digital marketing education as an effort to empower MSMEs to be able to utilize digital media in marketing their products. The methods used in this activity included preliminary interviews with Dompet Dhuafa Waspada Medan, delivery of material through seminars, question and answer sessions, and evaluation of participants' understanding using pre-tests and post-tests. The results of the activity showed an increase in participants' understanding of the basic concepts of digital marketing, as indicated by the post-test results, which were better than the pre-test results. Participants also showed enthusiasm and active involvement throughout the activity. Thus, this digital marketing education activity is considered effective in increasing the knowledge and readiness of Dompet Dhuafa Waspada Medan's SMEs to adopt digital marketing as a business development strategy.